2003
DOI: 10.1016/s1350-4177(02)00158-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of natural and synthesized aluminum-based composite materials with the aid of ultrasonic (cavitation) treatment of the melt

Abstract: The application of ultrasonic melt treatment to the production of natural and synthesized aluminum-based composite materials is considered in terms of underlying basic ideas and commercial implementations. It is shown that the ultrasonic cavitation treatment combined with microalloying of hypereutectic Al-Si natural composites (alloys) promotes the formation of structures suitable for further deformation. The use of highly impure starting materials becomes also possible. The combination of ultrasonic cavitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(85 citation statements)
references
References 2 publications
1
84
0
Order By: Relevance
“…Their results suggested that ultrasonic vibrations cause a significant reduction in the apparent contact angle between the particles and melt. Eskin 118) demonstrated that ultrasonic treatment combined with electromagnetic stirring can provide an uniformed distribution of 5-7 mm SiC particles in a Al-0.4%Si-0.7%Mg-20%SiC composite. They also concluded that cavitation promotes the wetting of ceramic particles by liquid aluminum and involves them into solidification process.…”
Section: Al-base Alloysmentioning
confidence: 99%
“…Their results suggested that ultrasonic vibrations cause a significant reduction in the apparent contact angle between the particles and melt. Eskin 118) demonstrated that ultrasonic treatment combined with electromagnetic stirring can provide an uniformed distribution of 5-7 mm SiC particles in a Al-0.4%Si-0.7%Mg-20%SiC composite. They also concluded that cavitation promotes the wetting of ceramic particles by liquid aluminum and involves them into solidification process.…”
Section: Al-base Alloysmentioning
confidence: 99%
“…INTENSE vibration of the liquid metal during solidification is known to refine microstructure, remove trapped gas, and reduce porosity. [1][2][3] Vibration can be achieved through various means: shaking the crucible, inserting a mechanical stirrer in the melt or, more commonly, using an ultrasonic horn e.g., in the DC casting of aluminum ingots. [3] In ultrasonic processing, frequencies around 20 kHz were found to be the most effective, [3] a fact attributed to the onset of cavitation.…”
Section: Valdis Bojarevics Georgi S Djambazov and Koulis A Periclmentioning
confidence: 99%
“…[1][2][3] Vibration can be achieved through various means: shaking the crucible, inserting a mechanical stirrer in the melt or, more commonly, using an ultrasonic horn e.g., in the DC casting of aluminum ingots. [3] In ultrasonic processing, frequencies around 20 kHz were found to be the most effective, [3] a fact attributed to the onset of cavitation. Gas micro-bubbles exist in the liquid either due to dissolved gases coming out of solution as the melt cools (e.g.,H 2 in Al), air trapped with oxides during mold filling, or gas attached to the surface of immersed particles.…”
Section: Valdis Bojarevics Georgi S Djambazov and Koulis A Periclmentioning
confidence: 99%
See 2 more Smart Citations